Porosity Measurement in Carbon-Fiber-Reinforced Polymer Composite Through Optical Microscopy Using ImageJ Software - Monticeli, Francisco [UNESP]; Voorwald, Herman [UNESP]; Cioffi, Maria Odila [UNESP] (Springer Nature, 2023)
Void morphology affects the mechanical behavior of carbon-fiber-reinforced polymer (CFRP) composites since void shape results in different stress concentration levels. Concerning of the importance of higher porosity characterization, this study proposes an automated methodology to measure the void content, morphology, and size of CFRP composites using ImageJ software (image processing) without generating toxic residues (sustainable void measurement). The results show that the variations in the threshold level strongly influence void measurement such that inappropriate levels can underestimate or overestimate the void content, highlight incorrect pixels, and prevent the measurement of the hole pore size. The most appropriate threshold level for CFRP composites was selected as 40 to ensure appropriate void content and size measurements. The proposed technique to measure the void content was validated by comparative analysis with a standard method. This study presents a careful analysis of porosity measurement parameters to quantify the void content, morphology, and size, and provides an automated methodology to configure the ImageJ software.
Keywords: Optical microscopy; Polymer composite; Sustainable measurement; Void